Preliminary Analysis Of Governance, Social Norms, and Behavioral Determinants of Household Participation in Marine-Linked Waste Management in Gorontalo Province, Indonesia - Nova Ulhasanah; Ari Rahman; Evi Sofiyah; I Wayan Koko; Mega Mutiara Sari (International Journal of Marine Engineering Innovation and Research, 2025)
This study investigates household willingness to adopt sustainable waste management practices in Gorontalo Province, Indonesia, a coastal region where unmanaged solid waste directly threatens marine natural capital such as mangroves, seagrass, and coral reef habitats. Using an extended Theory of Planned Behavior (TPB) framework, the research incorporated adaptive capacity as a governance-related antecedent to explain household pro-environmental behaviors. A cross-sectional survey of 63 respondents was conducted, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that attitudes had a modest effect on behavioral intentions (H4, p = 0.038), while subjective norms strongly predicted both perceived behavioral control (H2, p < 0.001) and intentions (H5, p < 0.001). Perceived behavioral control emerged as a decisive factor shaping intentions (H6, p = 0.002) and indirectly influencing behaviors (p = 0.012). Adaptive capacity significantly strengthened perceived behavioral control (H3, p = 0.028), confirming the importance of governance support in enabling household action. Finally, intentions strongly predicted actual behaviors (H7, p < 0.001), such as reducing single-use plastics and avoiding littering in coastal areas. These findings suggest that enhancing governance capacity, reinforcing social norms, and building household confidence are critical for aligning community waste practices with marine ecosystem protection.